MicroRNA-7 inhibits tumor growth and metastasis by targeting the phosphoinositide 3-kinase/Akt pathway in hepatocellular carcinoma - Fang, YuXiang; Xue, Jing-Lun; Shen, Qi; Chen, Jinzhong; Tian, Ling (Hepatology (Baltimore, Md.), 2012)
MicroRNAs (miRNAs) are known to be involved in carcinogenesis and tumor progression in hepatocellular carcinoma (HCC). Recently, microRNA‐7 (miR‐7) has been proven to play a substantial role in glioblastoma and breast cancer, but its functions in the context of HCC remain unknown. Here, we demonstrate that miR‐7 inhibits HCC cell growth and metastasis invitro and in vivo. We first screened and identified a novel miR‐7 target, phosphoinositide 3‐kinase catalytic subunit delta (PIK3CD). Overexpression of miR‐7 would specifically and markedly down‐regulate its expression. miR‐7‐overexpressing subclones showed significant cell growth inhibition by G0/G1‐phase cell‐cycle arrest and significant impairment of cell migration in vitro. To identify the mechanisms, we investigated the phosphoinositide 3‐kinase (PI3K)/Akt pathway and found that Akt, mammalian target of rapamycin (mTOR), and p70S6K were down‐regulated, whereas 4EBP1 was up‐regulated in miR‐7‐overexpressing subclones. We also identified two novel, putative miR‐7 target genes, mTOR and p70S6K, which further suggests that miR‐7 may be a key regulator of the PI3K/Akt pathway. In xenograft animal experiments, we found that overexpressed miR‐7 effectively repressed tumor growth (3.5‐fold decrease in mean tumor volume; n = 5) and abolished extrahepatic migration from liver to lung in a nude mouse model of metastasis (n = 5). The number of visible nodules on the lung surface was reduced by 32‐fold. A correlation between miR‐7 and PIK3CD expression was also confirmed in clinical samples of HCC. Conclusion: These findings indicate that miR‐7 functions as a tumor suppressor and plays a substantial role in inhibiting the tumorigenesis and reversing the metastasis of HCC through the PI3K/Akt/mTOR‐signaling pathway in vitro and in vivo. By targeting PIK3CD, mTOR, and p70S6K, miR‐7 efficiently regulates the PI3K/Akt pathway. Given these results, miR‐7 may be a potential therapeutic or diagnostic/prognostic target for treating HCC. (HEPATOLOGY 2012;55:1852–1862)